Efficacy, safety, and prognostic indicators of first-line sunitinib in patients with metastatic renal cell carcinoma: A single center experience - Ong, Teng Aik; Abd Ghafar, Nahjatul Kursyiah; Alip, Adlinda; Yap, Ning Yi; Saad, Marniza (Medknow Publications, 2018)
Background: We assessed the efficacy and safety of sunitinib as the first-line treatment in metastatic renal cell carcinoma (mRCC) patients. The predictors of survival and efficacy in mRCC as identified from previous studies, including the Memorial Sloan Kettering Cancer Center (MSKCC) and the International Metastatic RCC Database Consortium (IMDC) factors, were also evaluated. Patients and Methods: Data from 56 patients with mRCC, treated with sunitinib at our institute (2006-2014), were analyzed retrospectively. Prognostic factors for overall survival (OS) and progression-free survival (PFS) were evaluated using univariate and multivariate analyses performed by log-rank test and Cox regression. Results: Fifty-one (91.1%) patients received starting dose of sunitinib of 50 mg/day in 4/2 schedule. The median PFS was 12.7 months (95% confidence interval [CI], 4.5-20.9 months) and the median OS was 16.9 months (95% CI, 3.8-29.9 months). The objective response rate was 27.5%. Dose interruption and reduction due to toxicities were required in 37.5% and 60.7% of patients, respectively. The most common Grades 3-4 toxicities were hand-foot syndrome (HFS) (23.2%), thrombocytopenia (16.1%), and hypertension (14.3%). The Eastern Cooperative Oncology Group performance status ≥2, hemoglobin < lower limit of normal, neutrophil > upper limit of normal (ULN), platelet > ULN, no prior nephrectomy, metastatic sites >1, liver metastases, lymph node metastases, and development of HFS were independent prognostic factors. Conclusions: Sunitinib treatment has acceptable efficacy and safety profile in Malaysian mRCC patients. The MSKCC and IMDC factors are relevant for predicting survival in our patient cohort while HFS is a promising prognostic predictor which warrants further investigation.